Assessment of tax liability: A necessity or accessory? - Limuaco, Carmina (Animo Repository, 2002)
No civilized nation can exist without taxes. Taxes provide the fuel and lubricant that make governments function smoothly and well. Taxation plays a very significant role in the task of nation building. Taxes are the lifeblood of the government and so should be collected without unnecessary hindrance. On the other hand, such collection should be made in accordance with law, as any arbitrariness will negative the very reason for government itself. It is therefore necessary to reconcile the apparently conflicting interests of the authorities and the taxpayers so that the real purpose of taxation, which is the promotion of the common good, may be achieved. It has been ruled that assessment of a tax deficiency is not necessary to a criminal prosecution for tax evasion. The crime is complete when the violator has knowingly and willfully filed a fraudulent return with intent to evade and defeat the tax. Subsequently, the Court ruled in another case stating that, Before one is prosecuted for willful attempt to evade or defeat any tax, the fact that a is due must first be proved. Thus, making an assessment necessary. Which of the two opinions should prevail? Is there a standard that qualifies the implementation of assessment? The research is a modest attempt to analyze the merits and demerits of conducting assessments and otherwise prior to court proceedings. The study shall examine and give recommendations as to which will be more beneficial to the present system of taxation.